IEEE VTS 53rd Vehicular Technology Conference, Spring 2001. Proceedings (Cat. No.01CH37202)
DOI: 10.1109/vetecs.2001.944060
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for seamless handovers in GSM indoor wireless networks

Abstract: In this paper we consider the evolution of a GSM-based indoor corporate network, where base transceiver stations (BTS) are IP end-points of the local area network (LAN).Multiplexing capabilities of Real Time Protocol (RTP) payloads are exploited in order to efficiently transport TRAU (Transcoding and Rate Adaptation Unit) frames between each BTS and the BSC (Base Station Controller)/ Access Node. In this context two RTP connections are used to transmit downlink TRAU frames to both current BTS and candidate BTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This was based on 1991 field trials that were performed in an indoor wireless system that was based on CT3 technology that used Multi Carrier/ Time Division Multiple Access/ Time Division Duplex (MC/TDMA/TD) and operated at 900 MHz band [3]. Since then, numerous research papers and studies have investigated the issue of handover in indoor wireless networks [4]- [11]. The studies reported in [4]- [7] apply well-known techniques and ideas from the outdoor wireless networks to investigate and improve the handover performance of the indoor wireless networks.…”
Section: Introductionmentioning
confidence: 99%
“…This was based on 1991 field trials that were performed in an indoor wireless system that was based on CT3 technology that used Multi Carrier/ Time Division Multiple Access/ Time Division Duplex (MC/TDMA/TD) and operated at 900 MHz band [3]. Since then, numerous research papers and studies have investigated the issue of handover in indoor wireless networks [4]- [11]. The studies reported in [4]- [7] apply well-known techniques and ideas from the outdoor wireless networks to investigate and improve the handover performance of the indoor wireless networks.…”
Section: Introductionmentioning
confidence: 99%